1994
DOI: 10.1139/f94-010
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Size and Abundance of Juvenile Atlantic Cod (Gadus morhua) at an Inshore Site off Eastern Newfoundland

Abstract: Temporal variability in abundance and size of juvenile Atlantic cod (Gadus morhua) was studied at a shallow-water site in Trinity Bay, Newfoundland, from July 1982 to September 1983 and July 1989 to September 1990. Cod were collected with a small seine during the day and night. 0-group and 1-group cod predominated in the catch. Nighttime catches contained significantly more and larger cod than daytime catches primarily because 1-group cod were only collected at night. 1-group cod were not collected when water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 12 publications
5
40
0
Order By: Relevance
“…The first pulse occurs in August/ September, which is then followed by a 2 second pulse occurring approximately 30 d later (Methven & Bajdik 1994, Grant & Brown 1998a. In contrast, G. ogac settle in a single recruitment pulse in July/August (Laurel et al 2003a).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…The first pulse occurs in August/ September, which is then followed by a 2 second pulse occurring approximately 30 d later (Methven & Bajdik 1994, Grant & Brown 1998a. In contrast, G. ogac settle in a single recruitment pulse in July/August (Laurel et al 2003a).…”
Section: Methodsmentioning
confidence: 98%
“…Since the collapse of Atlantic cod populations off Newfoundland, Age 0 juvenile cod have been largely restricted to inshore areas (Dalley & Anderson 1997), where they are commonly associated with complex bottom habitats (Gotceitas et al 1997, Grant & Brown 1998a. Field experiments have demonstrated that these fish prefer to settle in eelgrass in July/August (Laurel et al 2003a) and remain there until late November, when they presumably move to deeper waters (Methven & Bajdik 1994). Eelgrass has been shown to reduce predation risk for Age 0 juvenile cod in both laboratory (Gotceitas et al 1997) and field (Linehan et al 2001, Laurel et al 2003b) experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Fish were unloaded into plastic tubs filled with seawater and identified, enumerated, and measured. Juvenile cod were considered pre-settled at < 60 mm and postsettled at > 60 mm (Methven & Bajdik 1994, Laurel et al 2003b). Fish were placed on ice immediately and frozen within 3 h of sampling.…”
Section: Methodsmentioning
confidence: 99%
“…Total lipids were 1.3 to 2.1% of wet weight, while previous reports on Newfoundland adult cod lipid composition showed that the flesh had 0.6% lipids while the liver contained 24% (Copeman & Parrish 2003). Settlement has previously been defined as 60 mm in standard length (SL) based on behavioral and pigmentation characteristics (Methven & Bajdik 1994, Laurel et al 2003a) and more recently based on biochemical characteristics (Copeman et al 2008). Table 4 shows that pelagic juvenile cod had low levels of total lipids and high proportions of PLs relative to TAGs, indicating few lipid reserves were present in the liver during settlement in the nearshore.…”
Section: Juvenile Codmentioning
confidence: 99%
“…High latitude temperate fishes, such as those found in Bonne Bay, experience large seasonal variations in temperature and day-length and these environmental factors may impart a natural seasonality to a fish assemblage (Nash, 1988). Other studies of temperate fish assemblages have found a decrease in catch size between spring and fall peaks (Allen, 1982;Methven and Bajdik, 1994). The data presented here are for fish species found in Bonne Bay in early summer.…”
Section: ! !mentioning
confidence: 46%